2011
DOI: 10.1182/blood.v118.21.2925.2925
|View full text |Cite
|
Sign up to set email alerts
|

Final Results of a Phase II Study Evaluating Lenalidomide in Combination with Low Dose Dexamethasone As First Line Therapy for Primary Plasma Cell Leukemia

Abstract: 2925 Primary plasma cell leukemia (PPCL) is an aggressive variant of multiple myeloma, accounting for 0.5–4% of all newly diagnosed myeloma cases and characterized by a short survival (generally less than 1 year), which is only moderately improved by transplant procedures. Novel agents seem to be able to ameliorate the poor clinical outcome of both primary and secondary leukemic phases of myeloma; however, no data are currently available on the use of lenalidomide as first line therapy in PPCL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Deletion of 13q by fluorescence in situ hybridization can be detected in up to 85% of cases of pPCL [2,7]. Deletions or mutation of p53 conferring adverse prognosis has been reported more frequently in PCL compared with MM (20%-56% in pPCL and 83% in sPCL versus 10%-15% in MM) [7,[15][16][17][18]. Chromosome 1 abnormalities are often seen in association with PCL [19].…”
Section: Genetic and Molecularmentioning
confidence: 99%
See 2 more Smart Citations
“…Deletion of 13q by fluorescence in situ hybridization can be detected in up to 85% of cases of pPCL [2,7]. Deletions or mutation of p53 conferring adverse prognosis has been reported more frequently in PCL compared with MM (20%-56% in pPCL and 83% in sPCL versus 10%-15% in MM) [7,[15][16][17][18]. Chromosome 1 abnormalities are often seen in association with PCL [19].…”
Section: Genetic and Molecularmentioning
confidence: 99%
“…Chromosome 1 abnormalities are often seen in association with PCL [19]. Amplification of 1q21 and deletion 1p21 are more common in PCL (46%-67% and 21%-44%, respectively) than in MM (30%-43% and 20%-36%, respectively), contributing to the worse prognosis in PCL [16][17][18][20][21][22]. Chang et al [20] reported a significantly greater increase in amplification of the cyclin-dependent kinase regulatory subunit 1 (CKS1B) gene in patients with PCL (62%) compared with patients with MM (relapsed, 52%; newly diagnosed, 36%; 0% in cases of monoclonal gammopathy of undetermined significance) (P < .001).…”
Section: Genetic and Molecularmentioning
confidence: 99%
See 1 more Smart Citation